Fluid inclusion hydrogen isotope data from speleothem WB-21-5-A - Paul S Wilcox (PANGAEA, 2023)
Deuterium measured from water was converted to temperature using several different transfer functions (parameters 5-7). The error applies to both temperature and temperature anomaly.
In: Wilcox, PS (2023): AK-1-FIT fluid inclusion data [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.964355